Direct observations of phase changes in Langmuir films of Cholesterol - R.D. Cadena-Nava (Revista Mexicana de Física, 2006)
We report isotherm, Brewster angle (BAM), ellipsometry and atomic force microscopy (AFM) studies of Langmuir films of cholesterol. At low surface pressures the Langmuir monolayers of cholesterol show a gas(G)-liquid condensed (LC) coexistence region in the range of 10 to 40◦ C. On further compression, the pure untilted LC phase region is entered, denoted by a rapid increase in surface pressure. Then, the monolayer is over compressed up to the collapse pressure, which is denoted by a long constant-pressure plateau. BAM observations show that the long plateau resembles a coexistence region between a 2D monolayer and 3D crystallites. The thickness of the crystallites measured in situ by ellipsometry are in good agreement with AFM measurements on transferred films on mica, which also reveal details of the large-size crystallites formed during collapse. The shape of the crystallites resembled those of the cholesterol monohydrate, but we found that they break over time into long, thinner crystal bars of anhydrous cholesterol. This phenomenon takes place at all temperatures, although at 10 and 20◦ C, the initial monohydrate crystals are shallow and small enough to allow a ready formation of the anhydrous crystal bars. At the two higher temperatures the monohydrate crystals are quite large, avoiding their total fragmentation into anhydrous crystal bars. Our results show for the first time a direct evidence that the initial monohydrate crystals formed during monolayer collapse are metastable against the anhydrous-type crystal bars, but the former crystals seem to increase their stability with the higher temperature.